Pelatihan Pembukuan Sederhana pada Kelompok Produksi Dangkrik “Gedhang Kripik” Dusun Kulubanyu Kabupaten Mojokerto - Iqbal Eka Sutawijaya (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Entrepreneurship is one of the factors in improving the economy in Indonesia through community economic empowerment. Entrepreneurship runs which one of is through Micro, Small and Medium Enterprises (MSME) is expected to utilize the available natural resources with properly, and then be able to have idea and creativity in manage them. One of the hamlets that produce banana plantations is Kulubanyu Hamlet. This hamlet is located in Tawangrejo Village, Mojokerto Regenct, East Java Province. The assistance was held by the village development team from State University of Surabaya for the residents of Kulubanyu Hamlet which resulted in product creations, namely Dangkrik “Gedhang Kripik”. An important factor in forming a new business by the residents of Kulubanyu Hamlet, except in product innovation, is also related to an understanding of financial management. So the village development team choosed to make counseling, training and mentoring activities for the Dangkrik business group regarding simple bookkeeping. The method that used by the village development team is simple bookkeeping training which runs for 2 months, the period of activity starting on August 18, 2019 and ending October 19, 2019. In the mentoring activity, the Kulubanyu Hamlet production group has been able to implementing simpe bookkeeping.